Analysing reconfigurable computing systems - Luk,W (2015)
The distinguishing feature of a reconfigurable computing system is that the function and the interconnection of its processing elements can be changed, in some cases during run-time. However, reconfigurability is a double-edged sword: it only produces attractive results if used judiciously, since there are various overheads associated with exploiting reconfigurability in computing systems. This chapter introduces a simple approach for analysing the performance, resource usage and energy consumption of reconfigurable computing systems, and explains how it can be used in analysing some recent advances in design techniques for various applications that produce run-time reconfigurable implementations. Directions for future development of this approach are also explored.